Creating and testing regulatory focus messages to enhance medication adherence. (June 2019) - O'Connor, Ashley; Ladebue, Amy; Peterson, Jamie; Davis, Ryan; Jung Grant, Susan; McCreight, Marina; Lambert-Kerzner, Anne
Objectives: Strategies were explored to improve patient adherence to cardioprotective medications by borrowing from a motivational framework used in psychology, regulatory focus theory. The current study is part of a larger randomized control trial and was aimed at understanding what written educational messages, based on patients' regulatory focus tendency, resonated with each individual as a potential reminder to take medications. This study was also aimed at understanding why messages resonated with the patients. Methods: Twenty veterans were tested for regulatory fitand presented with messages dependent on focus tendency. In-person semi-structured interviews were conducted to collect feedback of messages. An iterative analysis drawing primarily on matrix and reflexive team analyses was conducted. Result: Six promotion and six prevention messages emerged, such as "team up with your provider to create a combination of medications to prevent illness" and "Live your best life – Take your medications". Five themes related to types of health messages that spoke to patients' regulatory fit were discovered: relatability; empowerment and control; philosophy on life; relationship with provider and medications; and vocabulary effect on the impact of messages . Discussion: Motivational messages based on regulatory fit may be useful in improving patient medication adherence, leading to improved cardiovascular outcomes.